1997
DOI: 10.1073/pnas.94.18.9757
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles for DNA sequence identity and the mismatch repair system in the regulation of mitotic crossing-over in yeast

Abstract: Sequence divergence acts as a potent barrier to homologous recombination; much of this barrier derives from an antirecombination activity exerted by mismatch repair proteins. An inverted repeat assay system with recombination substrates ranging in identity from 74% to 100% has been used to define the relationship between sequence divergence and the rate of mitotic crossing-over in yeast. To elucidate the role of the mismatch repair machinery in regulating recombination between mismatched substrates, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
213
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(232 citation statements)
references
References 49 publications
17
213
2
Order By: Relevance
“…The clear distinction between msh6⌬ and pms1⌬ in our study suggests that there could be additional steps in the assessment of heterology in the more complicated case where a single strand invades duplex DNA and where Pms1p clearly plays a role (12,30,31). One difference between our assays and those used in previous studies is that SSA occurs without the assistance of the strand exchange protein Rad51 (50,51), whereas HO-induced gene conversions primarily proceed by strand exchanges mediated by Rad51p (52-54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clear distinction between msh6⌬ and pms1⌬ in our study suggests that there could be additional steps in the assessment of heterology in the more complicated case where a single strand invades duplex DNA and where Pms1p clearly plays a role (12,30,31). One difference between our assays and those used in previous studies is that SSA occurs without the assistance of the strand exchange protein Rad51 (50,51), whereas HO-induced gene conversions primarily proceed by strand exchanges mediated by Rad51p (52-54).…”
Section: Discussionmentioning
confidence: 99%
“…In both vegetative and meiotic yeast cells, the presence of even a few mismatches can markedly reduce recombination (12,(25)(26)(27)(28)(29)(30)(31). These studies have also shown that mismatch repair mutations including msh2, msh6, pms1, and mlh1 can elevate the level of recombination events involving homeologous sequences (32,33).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This aspect of recombination surveillance is thought to be carried out, in part, by proteins involved in the mismatch repair system [47]. In yeast, a rapid drop-off in recombination frequency vs. percent divergence is observed for repetitive elements, wherein the first few mismatches have a more suppressive effect on recombination than the addition of further mismatches [48]. As a consequence of the relationship between recombination and divergence, the particular TE ecology of a host genome, including the number and age of copy numbers, will have a significant impact on the potential for ectopic instability.…”
Section: Suppression Of Promiscuous Recombinationmentioning
confidence: 99%
“…Spies and Fishel (2015) provide a comprehensive discussion of heteroduplex rejection, the process by which mismatch repair enforces interaction between HR partners of sufficient homology. Already a single mismatch was found to reduce HR in a mismatch-repair-dependent fashion (Datta et al 1997). Use of the identical sister chromatid template in somatic cells allows setting a low threshold for heteroduplex rejection in mitotically growing cells.…”
Section: Reversibility Of Nascent D-loops: a Mechanism Of Antirecombimentioning
confidence: 99%